Antibiotics accumulate in Klebsiella pneumoniae liver abscesses but fail to eliminate antibiotic-tolerant populations - Michelle Angeles-Solano; Zajeba Tabashsum; Jamie D. Liu; Zachary J. Lifschin; Nikki J. Wagner; Kaleb J. Tyson; Liang Chen; Rani S. Sellers; Kimberly A. Walker; Yury Desyaterik; Elias P. Rosen; Sarah E. Rowe (Proceedings of the National Academy of Sciences, 2025)
Liver abscesses caused by hypervirulent Klebsiella pneumoniae (hvKp) can lead to severe metastatic complications, with mortality rates ranging from 5 to 40%. Even in the absence of antibiotic resistance, hvKp liver abscesses often respond poorly to treatment, sometimes requiring surgical resection. The reason for these poor outcomes remains unknown. Here, we established an hvKp wound model in outbred immunocompetent mice, which progresses to systemic infection and hepatic abscesses that were intractable to antibiotic therapy. Using a combination of quantitative and infrared matrix-assisted laser desorption electrospray ionization imaging mass spectrometry, we found that antibiotics fail to kill K. pneumoniae in liver abscesses, independently of resistance or spatial distribution of antibiotics. Our results show that antibiotic concentrations detected in the liver are sufficient to eradicate hvKp under standard in vitro conditions, but the continued presence of viable bacteria in vivo indicates that hvKp adopts an antibiotic-tolerant state within the liver. Notably, the inadequate antibiotic efficacy observed in our mouse studies mirrors clinical outcomes. These findings underscore the urgent need to elucidate the mechanism underlying hvKp tolerance, which could inform the development of novel therapeutic approaches.